Enhanced astronaut hygiene and mission efficiency: a novel approach to in-suit waste management and water recovery in spacewalks - Etlin, Sofia; Bielski, Luca; Rose, Julianna; Morales, Karen; Belman, Avery; Alexander, Emma; Li, Emma; Lin, Richard; Patel, Krishna; Rakhmonova, Stephanie; Walter, Claire; Mason, Christopher E. (Frontiers in Space Technologies, 2024)
The current waste management system within the Extravehicular Mobility Unit (EMU) consists of a disposable diaper—the Maximum Absorbency Garment (MAG)—that collects urine and feces during extravehicular activities (EVAs) that last up to 8 hours. Such exposure to waste for prolonged periods of time contributes to hygiene-related medical events, including urinary tract infections and gastrointestinal distress. Historically, to avoid using the MAG, astronauts have limited their food intake or eaten a low-residue diet before embarking on physically demanding spacewalks, reducing their work performance index (WPI) and posing a health risk. Furthermore, the current 0.95 L In-suit Drink Bag (IDB) will not provide sufficient water for more frequent, longer-range spacewalks, which carry greater potential for contingency scenarios requiring extended time away from a vehicle. High transport costs per pound to space and resource scarcity exacerbate these challenges, underscoring the need for water-efficient waste management. This paper introduces a novel in-suit urine collection and filtration system developed in the Mason Lab at Weill Cornell Medical College that could address these hygiene and hydration concerns. The device would collect astronaut urine via an external catheter and filter it using forward and reverse osmosis (FO-RO) into potable water, creating a sustainable and hygienic circular water economy, enhancing astronaut well-being. This research aims to achieve an 85% urine collection rate using a modified MAG. The modified MAG will be made of a flexible compression material lined with antimicrobial fabric, and urine is collected through a silicone urine collection cup, which differs for male and female astronauts to conform to anatomy. Urine collection via a vacuum pump is triggered by a humidity sensor that detects the presence of urine in the cup. The FO-RO filtration system targets a minimum of 75% water recovery, while consuming less than 10% of EMU energy. To meet health standards, the filtrate maintains low salt levels (<250 ppm NaCl) and effectively removes major urine solutes (urea, uric acid, ammonia). However, further research and testing are warranted to refine and implement these innovations for future space missions, contributing to the advancement of deep space exploration technologies and astronaut health and performance.